MENGETAHUI KOEFISIEN GESEK STATIK DAN KINETIS MELALUI KONSEP GERAK MELINGKAR BERATURAN - -, Hernawati (Teknosains, 2013)
Uniform circular motion is one of the topic in the physics lesson, in the learning process is very closely related to the observation or experiment. To find out the static friction coefficient and kinetic friction coefficient in the uniform circular motion, we made measurement on angular velocity, position of objects , mass of objects, angle between rope and horizontal surface, and rope tension. Data obtained was analyzed to determine the relationship between these variables, static friction coefficient, and kinetic friction coefficient. Analysis of this data done in two ways: calculating using the equation related, and through reading the graphicrelationship between two variables we obtained a quite small difference results from those analysis.Key words: uniform circular motion, static friction coefficient, and kinetic friction coefficient.